Pendampingan Penyampaian SPT Tahunan dalam Program Relawan Pajak - Hanik Susilawati Muamarah; Rd. Tatan Jaka Tresnajaya; Sopian Sopian (Universitas Mathla'ul Anwar Banten, 2022)
TAX VOLUNTEERS AND ANNUAL TAX RETURN REPORTİNG OF PERSONAL INCOME TAX. Every taxpayer has the obligation to submit an annual tax return, including individual taxpayers. However, many taxpayers experience problems in reporting, so they need assistance in filling out their annual tax return for individual taxpayers. The tax volunteer program organized by the PKN STAN tax center assists the Banten Regional Tax Office in providing assistance to individual taxpayers at KPP Pratama Pondok Aren. Tax Volunteers Team 9 provides online and offline assistance to taxpayers for 6 (six) days and successfully assists 41 taxpayers until they successfully report their tax returns. Obstacles found included account problems at djponline, application or server problems that were down, and incomplete documents. In the future, it is better to implement this program entirely offline, because it is more effective in terms of communication, it is faster to find out problems that occur and provide solutions.